Problems and Challenges of Community Campuses in Gandaki Province - Kaphle, Keshav Raj (Janaprakash Journal of Multidisciplinary Research, 2025)
This study explored the problems and challenges faced by community campuses in Gandaki Province, focusing on both QAA-accredited and QAA in process campuses. Using a qualitative research design with a descriptive phenomenological approach, data were collected from ten purposively selected campus chiefs through open-ended questions. Thematic analysis revealed that financial constraints, inadequate infrastructure, shortages of qualified full-time faculty, low student enrollment, and high dropout rates are determined problems across campuses. Faculty motivation, professional development, and research engagement were found to be limited, while weak governance, political interference, and insufficient community support further weaken institutional effectiveness. Campuses also face challenges in aligning academic programs with labor market needs, implementing modern teaching methods, and supporting long-term growth. QAA-accredited campuses generally demonstrate better governance, faculty quality, student engagement, and infrastructure compared to campuses still undergoing accreditation. The study recommends dedicated funding, income-generating programs, faculty recruitment and development, modernization of curricula, ICT integration, research support, strengthened governance, and active community engagement to enhance sustainability, academic quality, and student success. These findings provided critical insights for policymakers, campus administrators, and stakeholders to improve the performance and resilience of community campuses in Nepal.